IMPLIKASI MODEL UTAUT DALAM MENJELASKAN FAKTOR NIAT DAN PENGGUNAAN SIPKD KABUPATEN TABANAN - Widnyana, Ida I Dewa Gede Paramarta; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 11 No 2 (2015), 2015)
Model Unified Theory of Acceptance and Use of Technology (UTAUT) used in this study to explain factors of interest and the use of financial management information system ( SIPKD ) on 42 SKPDs Tabanan Regency. The results of this study are based on 77 answers SIPKD operators who responded. Respondents were determined using nonprobability and purposive sampling technique. Researchers distributed questionnaires to collect data and tested by multiple linear regreli analysis techniques. UTAUT were tested in this study are prepared on the 2 dependent variable is the intention to use and system usage behavior as well as four independent variables are expectations of performance, effort expectancy, social influence and support conditions. Results of the study showed no effect on the effort expectancy of intention to use but performance expectations and social influence significant positive effect on intention to use . Supporting conditions and interest significant positive effect on system usage behavior .
Keywords: UTAUT, intention to use , used system